Corporate actors, the UN Sustainable Development Goals and Earth System Governance: A research agenda. (April 2019) - Dahlmann, Frederik; Stubbs, Wendy; Griggs, Dave; Morrell, Kevin
The Anthropocene requires significant shifts and innovation in policy as well as human action and behavior. While much research attention has focused on society and policy makers, we know significantly less about how businesses exercise agency as part of Earth System Governance such as their contribution to the UN Sustainable Development Goals. Concerns are mounting over how large corporations are being governed and how businesses generally should operate in the Anthropocene. In this Perspective, we outline three potential high-impact areas for interdisciplinary research: (1) integrating global goals into corporate target-setting; (2) integrating global goals into codes of corporate governance; and (3) integrating global goals into new business models. We argue that understanding the role that corporate actors play in Earth System Governance is of vital importance to ensure efforts and outcomes are effective and equitable.